Antiangiogenic Activity of Aerva lanata Flowers: In Vitro and In Vivo Evaluation - Ramdhan G; D.V.R.N., Bhikshapathi (Natural Products Journal, The, 2023)
Background: A well-known traditional herb Aerva lanata is widely used in India for the management of different ailments, including urolithiasis. Objective: In the current research, flowers of Aerva lanata were chosen for isolation of active constituents and screened for antiangiogenic and anticancer potentials, as literature supports that those flowers have highest quantity of natural constituents compared with the other parts of the plant. Materials and Methods: Hydroalcoholic (80%-water, 20%-alcohol) extract of Aerva lanata flowers was prepared. Antiangiogenic activity was screened by chick chorioallantoic membrane assay (CAM) (in vivo) and sponge implantation method (SIM) (in vivo). Anti-cancer potency was screened by cell migration (in vitro), tube formation assay (in vitro) and cell proliferation assay (in vitro). Results: The results of the test groups were matched up to control group by applying one-way ANOVA, followed by a post hoc and Dunnett’s test. In CAM assay method, significant branching points and angiogenic score was obtained at 10-5 M and 10-4 M. Considerable decline was observed in sponge weight and formation of blood vessels and hemoglobin content (Hb) at various concentrations of hydroalcoholic extract of Aerva lanata flower (HAL) in SIM. The study on human umbilical vein endothelial cells displayed major inhibition of proliferation along with the reduction in network length of cord-alike tubes in a dosage-dependent pattern. Conclusion: Aerva lanata has shown potent antiangiogenic and anticancer effect in a dosedependent manner.
Keywords: Aerva lanata